Đánh giá sự xuất hiện và rủi ro tiềm năng của các kháng sinh quinonoles, sulfonamides và trimethoprim đối với môi trường nước và trầm tích của Hồ Tây và hồ Trúc Bạch - Thanh Yên, Phạm Thị; Trung, Nguyễn Quang; Hải, Huỳnh Trung (Vietnam Journal of Chemistry, 2016)
The occurrence of the 9 antibiotics (SMX, STZ, SMZ, SMR, TRI, NOR, CIP, ENR, OFL) in water and sediments of the West and Truc Bach Lakes showed the antibiotic concentrations in water samples are ranging from below the detection limit (BDL) to 104.3 ng/L and those in the sediment samples are from the BDL to 23.81 ng/g. From the target analytes investigated in West Lake and Truc Bach Lake, SMX is detected at the highest concentrations of 89.7 ng/L and 104.3 ng/L in the water samples respectively and CIP is having the highest concentrations of 10.68 ng/g and 23.81 ng/g in the sediment samples respectively. We have found no traces of STZ and SMR in water and sediments from the West Lake and similarly, detected none of STZ and SMZ residues in samples from Truc Bach Lake. An environmental risk assessment conducted for nine antibiotics in sediments and water of West Lake and Truc Bach reveals the two antibiotics (CIP and OFL) are having the hazardous quotient (HQ) greater than 1, posing a high ecological risk to some sensitive organisms.